Pengaruh Struktur Kepemilikan Saham, Ukuran Perusahaan, dan Profitabilitas Terhadap Pengungkapan Sukarela - Maesaroh, Maesaroh; Aisyiah, Helti Nur (JIFA (Journal of Islamic Finance and Accounting), 2020)
This study aims to determine the effect of shareholding structure, company size, and profitability on voluntary disclosure. The dependent variable used in this study is the managerial and institutional ownership, company size, and company profitability. While the independent variable in this study is voluntary disclosure. This study used the population of all manufacturing companies that were continuously listed on the Indonesia Stock Exchange during 2017-2018 period. This study used 61 companies multiplied by two years of the study period obtained 122 samples. Sampling technique used was purposive sampling with certain criteria to eliminate companies from the population. The study found reveal that managerial and institutional ownership had negative influence on voluntary disclosure, while company size variables had a positive influence on voluntary disclosure. Whereas the profitability had no significant influence on voluntary disclosure. Keywords: voluntary disclosure, company ownership structure, company size, profitability